Construction of a Synthetic Index for Institutional Performance in Colombian Municipalities - Ardila Delgado, Armando; García Solano, Diego José (Revista del CLAD Reforma y Democracia, 2017)
This document presents in a detailed manner all the elements necessary for estimating a synthetic index for institutional performance in local governments, including a sample of 128 municipalities in Colombia. Through a principal components analysis, our research studies the salient points for an efficient public performance in a local level and establishes a ranking for the municipalities in the sample. In view of the Colombian peace process, this methodological exercise allows local government to know in which components they have bad performance, to allocate more resources to tackle those problems and allows nationwide institutions to aid those municipalities in the last positions.
Keywords: Performance Indicators; Municipalities; Municipal Development; Proposal; Colombia